Secondhand smoke exposure and asthma outcomes among African-American and Latino children with asthma. Issue 11 (13th June 2018) - Neophytou, Andreas M; Oh, Sam S; White, Marquitta J; Mak, Angel C Y; Hu, Donglei; Huntsman, Scott; Eng, Celeste; Serebrisky, Denise; Borrell, Luisa N; Farber, Harold J; Meade, Kelley; Davis, Adam; et al.
Abstract : Background: Secondhand smoke (SHS) exposures have been linked to asthma-related outcomes but quantitative dose–responses using biomarkers of exposure have not been widely reported. Objectives: Assess dose–response relationships between plasma cotinine-determined SHS exposure and asthma outcomes in minority children, a vulnerable population exposed to higher levels of SHS and under-represented in the literature. Methods: We performed analyses in 1172 Latino and African-American children with asthma from the mainland USA and Puerto Rico. We used logistic regression to assess relationships of cotinine levels ≥0.05 ng/mL with asthma exacerbations (defined as asthma-related hospitalisations, emergency room visits or oral steroid prescription) in the previous year and asthma control. The shape of dose–response relationships was assessed using a continuous exposure variable in generalised additive logistic models with penalised splines. Results: The OR for experiencing asthma exacerbations in the previous year for cotinine levels ≥0.05 ng/mL, compared with <0.05 ng/mL, was 1.40 (95% CI 1.03 to 1.89), while the OR for poor asthma control was 1.53 (95% CI 1.12 to 2.13). Analyses for dose–response relationships indicated increasing odds of asthma outcomes related with increasing exposure, even at cotinine levels associated with light SHS exposures. Conclusions: Exposure to SHS was associated with higher odds of asthma exacerbations and having poorly controlled asthma with an increasing dose–response even at low levels of exposure. Our results support the conclusion that there are no safe levels of SHS exposures.